Minnelide synergizes with conventional chemotherapy by targeting both cancer and associated stroma components in pancreatic cancer. (1st July 2022) - Modi, Shrey; Giri, Bhuwan; Gupta, Vineet K.; Lavania, Shweta; Sethi, Vrishketan; Sharma, Nikita S.; Pandey, Somnath; Vickers, Selwyn; Dudeja, Vikas; Saluja, Ashok K.
Abstract: Addition of nab- paclitaxel to gemcitabine offers a survival benefit of only 6 weeks over gemcitabine alone at a cost of increased toxicity in PDAC. The goal of the present study is to evaluate the efficacy of Minnelide, a water-soluble prodrug of triptolide, in combination with the standard of care regimen for chemotherapy with the added advantage of reducing the doses of these drugs to minimize toxicity. Pancreatic cancer cell lines were implanted subcutaneously or orthotopically in athymic nude or C57BL/6J mice. Subsequently, animals were randomized and received saline or minnelide or full dose chemotherapy or low dose chemotherapy or minnelide in combination with low dose chemotherapy. Our results show that a combination of low doses of Minnelide with Gemcitabine + nab- paclitaxel significantly inhibited tumor progression and increased the survival of tumor-bearing mice in comparison with conventional chemotherapy alone. Moreover, combination therapy significantly reduced cancer-related morbidity by decreasing ascites and metastasis and effectively targeted both cancer and the associated stroma. In vitro studies with a combination of low doses of triptolide and paclitaxel significantly decreased the cell viability, increased apoptosis and led to significantly increased M-phase cell cycle arrest in various pancreatic cancer cell lines as compared to either drug alone. Our results show that Minnelide synergizes with conventional chemotherapy leading to a significant reduction in the doses of these toxic drugs, all the while achieving better efficacy in the treatment of PDAC. This combination effectively targeted both the cancer and the associated stromal components of pancreatic cancer. Highlights: Combination of low doses of Minnelide and Standard-of- care inhibited tumor growth and effectively target tumor stroma in Pancreatic Cancer. Minnelide in combination with paclitaxel cause cell death in pancreatic cancer cell by inducing M phase arrest. Combination of low doses of Minnelide and standard-of- care chemotherapy shows better response compared to conventional dose of standard-of- care chemotherapy in various preclinical mouse models.